Novo ENEM: experiências de participação, sentidos e significados atribuídos pelos estudantes à política - Oliveira, Ivan dos Santos (Universidade do Vale do Rio dos Sinos, 2013)
Bearing in mind the importance that evaluation public policy of the new ENEM (High School National Exam) has achieved, this research aims – as main objectives, through the point of view of the students who had taken the exam, to comprehend what their senses and meanings about the new ENEM are. As well as understanding this policy influence and other large scale evaluations in their school experiences. For this purpose, the policy cycle approach of Stephen J. Ball was taken as reference theoretical patterns, which were bases to realize the execution mechanisms of the processes involving policies in general meanings, considering important the action exercised by the subjects as a crucial aspect for its understanding along with the Discourse Analysis Theory justified by Michel Pêcheux, as the base theory of the analysis in order to be aware of the senses and meanings built by the research collaborators through the language. By analyzing the data produced during the interviews it was possible to realize that lack of communication and dialog was frequent within the collaborators school environment, making of these the atmosphere set up to be applied foreign evaluations. It was evinced the lack of perception in terms of the influence of the foreign evaluations in a huge level by the research collaborators inside their school environment. Regarding the influence and repercussion of the new ENEM within the school surroundings, it was possible to verify the existence of two distinct realities, one for each: public and private school. Concerning the senses and functions ascribed by the students to the policy of the new ENEM, it was acknowledged that the official discourse exerts strong influence and is present in the collaborators perception when they evoke a political sense: the self-evaluation, the process participation democratization, the prompting for high school and superior education admission changes. Finally, it was possible to comprehend that, even for students that estimate their participation in this process as positive, many times these experiences may configure as wearing, unpleasant and many times traumatic, because of factors that take action before the exam, throughout the application and subsequent to the test.
Keywords: Novo ENEM; Avaliação em larga escala; Sentidos; Significados; Participação; New ENEM; Large scale evaluation; Senses; Meaning; Participation; ACCNPQ::Ciências Humanas::Educação